An unusual outbreak of norovirus associated with a Halloween-themed swimming pool party in England, 2016 - Paranthaman, Karthik; Pringle, Ellen; Burgess, Alison; Macdonald, Neil; Sedgwick, James (Euro surveillance : bulletin européen sur les maladies transmissibles, 2018)
In October 2016, an outbreak of norovirus occurred among attendees of a Halloween-themed party at a public swimming pool in the south-east of England. Norovirus genogroup II was confirmed in 11 cases. In the retrospective cohort study of pool users, 68 individuals (37 female and 31 male), with a median age of 11 years (range: 0–50 years), met the case definition of developing diarrhoea or vomiting between 6 and 72 h after the pool visit. Multivariable analysis showed that increasing age was associated with a reduced risk of illness (odds ratio = 0.91; 95% confidence interval: 0.83–0.99). Pool behaviours (swallowing water) and the timing of visit (attending pool party after automatic dosing system was switched off) were independently associated with increased risk. Environmental investigations revealed that the automatic dosing system was switched off to reduce chlorine levels to an intended range of 0.5–1 parts per million to facilitate the use of a commercial red dye. There was a lack of compliance with the operator's own pool operating procedures, particularly on maintaining effective chlorine levels in pool water, recording of test results and recording of actions undertaken. This outbreak highlights the risks of lowering chlorine levels when using pool water colourants.